Sociodemographic Effects on Financial Inclusion: Implications from Online Transaction in Developing-8 Countries - Wardani, Dyah Titis Kusuma; Khusniati, Navi'ah; Darsono, Susilo Nur Aji Cokro (Economics and Finance in Indonesia, 2023)
The world has reached the industry 4.0, where technological developments have been widely applied to electronic payment, with no exception on Muslim countries. This study aims to investigate association between sociodemographic and financial inclusion in country D-8 in the probability of using online financial transactions. Using The Global Findex 2017 from D-8 Organization for Economic Cooperation included in OIC countries and the logistic regression, this study explores the effect of sociodemographic namely gender, education, income status and working status on online financial transactions users. Using control variables such as Gross Domestic Product (GDP), Inflation and Exchange reta, results show that, there is a gender imbalance between men and women in using online transaction to access formal services. On the other hand, individuals who have higher level of education, upper-middle income and high-income, and those who work are more financially inclusive in using online transaction. In conclusion, those with higher sociodemographic status are more likely to use online transaction to access formal financial services. The government and third parties can use this study as policy recommendations for expanding online transaction as well as financial inclusion in developing Muslim countries.